Possible protective role of the absence of Hyrtl’s anastomosis in monochorionic pregnancy: exploratory case series - Ziling Liu; Jie Ruan (Frontiers in Medicine)
ObjectiveHyrtl’s anastomosis, an intra-arterial shunt, serves a protective function in singleton placentas. Our team previously documented a case of a monochorionic (MC) twin placenta lacking Hyrtl’s anastomosis. However, research on the impact of absent Hyrtl’s anastomosis in twin placentas remains limited.MethodsIn the present study, we perfused over 70 cases of MC placentas and identified three additional cases exhibiting the same characteristics.ResultsThe absence of Hyrtl’s anastomosis was found to be present in two cases with severe placental territory discordance and one case of a MC triamniotic pregnancy with reversed arterial perfusion sequence, all of which resulted in uneventful pregnancy courses.ConclusionThe absence of Hyrtl’s anastomosis appears to have a protective effect in MC placentas, contrary to its effect in singleton placentas.